Upaya Pelindungan Rangka Manusia dan Peti Kubur Kayu di Situs Gua Latea I dan II, Poso, Sulawesi Tengah - Putri, Novialita Ridimas; Anggraeni, Anggraeni (Universitas Negeri Gorontalo, 2025)
Latea Cave I and II cultural heritage sites are burial sites using wooden coffins in Tentena, Poso, and Central Sulawesi. The cave is a tourist destination for foreign and local tourists. Latea Caves I and II have more skull and yumu finds than any other site around Tentena. Thus, this research was carried out by observing tourist behaviour and the conditions of the surrounding environment. The results of the observations showed that factors that could damage the behaviour of tourists were rodents, such as rats, as well as humid environmental conditions. So the solution that can be given is to improve the performance of custodians as well as tour guides by adding facilities such as rubbish bins and monitoring the conservation that has been carried out. To get rid of rodents, you can do it in various ways, including by installing rat traps periodically.